Are distal radius fracture classifi cations reproducible? Intra and interobserver agreement - Belloti, João Carlos; Tamaoki, Marcel Jun Sugawara; Franciozi, Carlos Eduardo da Silveira; Santos, João Baptista Gomes dos; Balbachevsky, Daniel; Chap, Eduardo Chap; Albertoni, Walter Manna; Faloppa, Flávio (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Various classifi cation systems have been proposed for fractures of the distal radius, but the reliability of these classifications is seldom addressed. For a fracture classification to be useful, it must provide prognostic signifi cance, interobserver reliability and intraobserver reproducibility. The aim here was to evaluate the intraobserver and interobserver agreement of distal radius fracture classifi cations. DESIGN AND SETTING: This was a validation study on interobserver and intraobserver reliability. It was developed in the Department of Orthopedics and Traumatology, Universidade Federal de São Paulo — Escola Paulista de Medicina. METHOD: X-rays from 98 cases of displaced distal radius fracture were evaluated by fi ve observers: one third-year orthopedic resident (R3), one sixth-year undergraduate medical student (UG6), one radiologist physician (XRP), one orthopedic trauma specialist (OT) and one orthopedic hand surgery specialist (OHS). The radiographs were classifi ed on three different occasions (times T1, T2 and T3) using the Universal (Cooney), Arbeitsgemeinschaft für Osteosynthesefragen/ Association for the Study of Internal Fixation (AO/ASIF), Frykman and Fernández classifi cations. The kappa coeffi cient (κ) was applied to assess the degree of agreement. RESULTS: Among the three occasions, the highest mean intraobserver k was observed in the Universal classifi cation (0.61), followed by Fernández (0.59), Frykman (0.55) and AO/ASIF (0.49). The interobserver agreement was unsatisfactory in all classifi cations. The Fernández classifi cation showed the best agreement (0.44) and the worst was the Frykman classifi cation (0.26). CONCLUSION: The low agreement levels observed in this study suggest that there is still no classifi cation method with high reproducibility.